THE CULTIVATION OF CRABS RHIZOPHORA ( Scyila serrata ) WITH A KIND OF THE WEFT OF WHICH DIFFERENT - Anisa latipah; Rusliadi '; Usman M Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from March to April with 2013, and held at the Fisheries Agency and Serdang Bedagai Regency in the North Sumatra town of Pari. The purpose and benefits of this research is to investigate the kind of feed which was able to speed growth and accelerate the growth of crab. The method is applicable in the experimental methods are using design random complete ( ral ) one factor by 4 standard treatment. Treatment applied in this research is the feed, Rucah Fish+ pellets, Pellet+ Snails Mas, Rucah Fish, Snails Mas. The best results of the best of this research namely by feed on fish rucah with the average growth absolute weights absolute 56,67 grams, the average daily growth rate of 5,37% and average egg growth rara of 488,89%.Keywords: Mangrove Crabs (Scylla serrata), type of feed, growth egg